Mobility management schemes in NEMO to achieve seamless handoff: a qualitative and quantitative analysis - Islam, Shayla; Hassan Abdalla Hashim, Aisha; Saeed, Rashid Abdelhaleem; Khalifa, Othman Omran; Hasan, Mohammad K.; Mahmoud, Omer; Daoud, Jamal Ibrahim; Hameed, Shihab A. (INSI Publications, 2011)

(untitled)
Recently, ITEF standardized the management mechanism of NEMO BSP to support Network Mobility which is an extension of Mobile IPv6 (MIPv6) that inherits all the drawbacks of Mobile IPv6, such as inefficient routing path, single point of failure, high handover latency, packet loss, and high packet overhead. Therefore route optimization and multihoming technique in NEMO is becoming most important area for current researcher. The objective of this paper is to analyze some mobility management schemes in order to achieve seamless handoff in NEMO as well as available solutions will be discussed for future analysis. Furthermore, it highlights the strengths and the limitations of these schemes. Both the qualitative and the quantitative evolutions of these schemes are also presented here.